2015
DOI: 10.1128/mcb.01401-14
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Transcription Elongation by the XPG-TFIIH Complex Is Implicated in Cockayne Syndrome

Abstract: XPG is a causative gene underlying the photosensitive disorder xeroderma pigmentosum group G (XP-G) and is involved in nucleotide excision repair. Here, we show that XPG knockdown represses epidermal growth factor (EGF)-induced FOS transcription at the level of transcription elongation with little effect on EGF signal transduction. XPG interacted with transcription elongation factors in concert with TFIIH, suggesting that the XPG-TFIIH complex serves as a transcription elongation factor. The XPG-TFIIH complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…Thus, the true biological relevance of XPC in developmental gene expression programs remains elusive. XPG–TFIIH has also been shown to interact with factors involved in transcription elongation, suggesting that defects in this association could account for certain CS features in XPG/CS patients …”
Section: Linking Ner To Transcription Demandsmentioning
confidence: 99%
“…Thus, the true biological relevance of XPC in developmental gene expression programs remains elusive. XPG–TFIIH has also been shown to interact with factors involved in transcription elongation, suggesting that defects in this association could account for certain CS features in XPG/CS patients …”
Section: Linking Ner To Transcription Demandsmentioning
confidence: 99%
“…Xeroderma pigmentosum type G (XPG) proteins (also known as excision repair cross-complementation group 5) belong to the FEN-1 family of structure-specific nucleases and play an essential role in both NER pathways, transcription-coupled repair and global genome repair [1,[4][5][6][7][8]. Mutations in XPG proteins may also lead to the Cockayne syndrome, associated with severe developmental retardation, dwarfism and neurological abnormalities [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…These studies furthermore revealed a role for Xpa and Xpf in this process ( 26 ), what we here could recapitulate: in our hands KD of Xpf and Xpa caused a similar attenuation of p21 induction as Xpg KD. Additional mechanisms may play into our observation, too, as Xpg potentially also enhances transcriptional elongation of p21 mRNA ( 39 ). Moreover, p53 target genes such as Puma are induced both by glucocorticoid treatment and IR ( 40 ).…”
Section: Discussionmentioning
confidence: 98%